An exploration of the symbolic world of Proverbs 10:1–15:33 with specific reference to ‘the fear of the Lord’ - Venter, P.M. (Pieter Michiel), 1947- (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.